TINJAUAN YURIDIS ATAS PERJANJIAN ASURANSI KREDIT TERHADAP NASABAH ATAS AGUNAN KLAIM YANG DIBAYARKAN OLEH ASURANSI - Hendrawan, Muhammad Galih; Kamarullah, Kamarullah; Itasari, Endah Rantau (Faculty Of Law, Universitas Tanjungpura, 2024)
Abstract This research intends to conceptually examine the legal status of credit insurance agreements on customer collateral and customer obligations towards claims paid by insurance. This research uses a normative or doctrinal legal research form that is descriptive analysis. The data used is secondary data obtained through literature studies. The analysis of this research data was carried out qualitatively through legal argumentation reasoning. From the results of the study, it was found that the status of collateral guaranteed to the bank in credit insurance is entirely the responsibility of the bank and if there is a default by the debtor, the collateral will be an addition to the repayment of the remaining credit if the claim made by the insurance party to the bank is not sufficient for the nominal remaining credit of the debtor. The debtor's obligations have been clearly regulated in the credit agreement clause where the debtor must insure immovable property that will be used as collateral in the credit agreement by burdening it with a mortgage. Keywords: Agreements; Bank